THE EFFECT OF USING SMALL GROUP DISCUSSION IN READING COMPREHENSION OF FACTUAL REPORT TEXT - Adeliza Meisy; Suparmi; Rosi Kumala Sari (JELLT (Journal of English Language and Literature Teaching), 2022)
This study aimed (1) To find out the students' reading comprehension of Factual Report text before using the small group discussion technique for class XI TITL at SMKN 1 Padang. (2) To find out the reading comprehension of students on Factual Report text after using the small group discussion technique for class XI TITL at SMKN 1 Padang. (3) To find out whether or not there is a significant effect of using the small group discussion method for students' reading comprehension on reporting factual text for class XI TITL at SMKN 1 Padang. This research is Class Action Research. The techniques for collecting the data are documentation and testing. The subjects of this study were 29 students for class XI TITL-A. The results of the data have been 54% of students did not understand reading comprehension, with scores below the average. after the second cycle using small group discussion, all student scores increased above the average to 94%, which increased to 41% above the average. With the formation of small group discussions, students' reading comprehension has increased.